1990
DOI: 10.1111/j.1570-7458.1990.tb01356.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of induced resistance in soybean on the development and nutrition of the soybean looper and the Mexican bean beetle

Abstract: Standard gravimetric technique was used to assess the effect of induced resistance in soybean on the consumption and utilization of food by the Mexican bean beetle (MBB), Epilachna varivestis, and the soybean looper (SBL), Pseudoplusia includens. Induced resistance had significant retarding effects on the development and growth of both SBL and MBB. SBL fed leaves of previously injured soybean plants had a 8.5% longer developmental time through the entire larval stage and a 10.4% lower pupal weight than larvae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Induced resistance in soybeans has been measured in previous studies both by bioassay and by tracking increases in various substances, including PIs, after damage (e.g., Kraemer et al 1987;Lin and Kogan 1990;Bi et al 1994;Botella et al 1996;Underwood 1998). In this study we focus on cystein PIs because they are known to inhibit the digestive enzymes of several beetle species (Hines et al 1991;Zhao et al 1996), and thus might be likely to affect Mexican bean beetles.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Induced resistance in soybeans has been measured in previous studies both by bioassay and by tracking increases in various substances, including PIs, after damage (e.g., Kraemer et al 1987;Lin and Kogan 1990;Bi et al 1994;Botella et al 1996;Underwood 1998). In this study we focus on cystein PIs because they are known to inhibit the digestive enzymes of several beetle species (Hines et al 1991;Zhao et al 1996), and thus might be likely to affect Mexican bean beetles.…”
Section: Methodsmentioning
confidence: 98%
“…Much is now understood, especially for a few species such as tobacco, tomato and soybeans, about how plant chemistry can change after herbivore attack [see Karban and Baldwin (1997) for review]. Many studies have also demonstrated that previously damaged plants can lower insect preference and performance in the laboratory and field (e.g., Edwards et al 1985;Haukioja and Neuvonen 1985;Karban 1986;Lin and Kogan 1990;Bi et al 1994;Underwood 2000), and that chemicals that change after damage can inhibit insect digestion or lower performance in the laboratory (e.g., Johnson et al 1989;Bi et al 1994;Zhao et al 1996). A smaller number of theoretical and field studies indicate conditions that should favor the evolution of induced versus constitutive resistance (Adler and Karban 1994;Astrom and Lundberg 1994;Zangerl and Rutledge 1996), and suggest that induced resistance should have important consequences for herbivore populations (Rhoades 1985;EdelsteinKeshet and Rausher 1989;Underwood 1999), and for the predators of herbivores (Thaler 1999).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Induction enhances soybean resistance to insects and pathogens (Lin and Kogan 1990, Dann et al, 1998, Thaler 1999. Induced responses produce volatiles that act as a direct defense against the herbivores (Karban and Baldwin 1997) and as an attractant to parasitoids in the form of indirect defense (Turlings et al 1995, Dicke andLoon 2000).…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of herbivore population dynamics, induced resistance is any change in a plant resulting from damage that imparts a negative effect on herbivores (Karban and Baldwin 1997). Insect herbivory has been shown to induce resistance in soybean plants (Lin et al, 1990b, Fischer et al, 1990, Lin and Kogan 1990) against the soybean looper, Pseudoplusia includens and the Mexican bean beetle, Epilachna varivestis.…”
Section: Introductionmentioning
confidence: 99%